The Invisible Universe The Story of Radio Astronomy - Verschuur, Gerrit (Astronomers' Universe, 2015)
Hidden from human view, accessible only to sensitive receivers attached to huge radio telescopes, the invisible universe beyond our senses continues to fascinate and intrigue our imaginations. Closer to home, in the Milky Way galaxy, radio astronomers listen patiently to the ticking of pulsars that tell of star death and states of matter of awesome densities. All of this happens out there in the universe hidden from our eyes, even when aided by the Hubble Space Telescope. This is the story of radio astronomy, of how radio waves are generated by stars, supernova, quasars, colliding galaxies and by the very beginnings of the universe itself. The author discusses what radio astronomers are doing in the New Mexico desert, in a remote valley in Puerto Rico, and in the green Pocahontas Valley in West Virginia, as well as dozens of other remote sites around the world. With each of these observatories, the scientists collect and analyze their data, "listening" to the radio signals from space in order to learn what, or perhaps who, is out there as well. The author specifically highlights enormous changes that have occurred in the field over the past 50 years, including the political reality of radio astronomy and what that could mean for the future.